On Pseudospherical Smarandache Curves in Minkowski 3-Space - Esra Betul Koc Ozturk; Ufuk Ozturk; Kazim Ilarslan; Emilija Nešović (Journal of Applied Mathematics)
In this paper we define nonnull and null pseudospherical Smarandache curves according to the Sabban frame of a spacelike curve lying on pseudosphere in Minkowski 3-space. We obtain the geodesic curvature and the expressions for the Sabban frame’s vectors of spacelike and timelike pseudospherical Smarandache curves. We also prove that if the pseudospherical null straight lines are the Smarandache curves of a spacelike pseudospherical curve α, then α has constant geodesic curvature. Finally, we give some examples of pseudospherical Smarandache curves.